Fadiga por compaixão em médicos veterinários: uma ferida invisível - Veleda, Patrícia Alvez (2022)
The assistance to a being in suffering moves the entire organism of the person who provides it, demanding maximum tension and vigilance. Veterinarians are health professionals, who constantly deal with traumatic events, pain, suffering and death, being subjected to great emotional exhaustion. These events are part of their daily care routine, subjecting workers to stress and professional exhaustion. In this context, the physical and emotional exhaustion generated by empathy originated from treating the pain of others might lead to the development of compassion fatigue. This disorder has been considered the main threat to the mental health of such professionals. In the light of this, it is essential to be ready to provide assistance, even in the face of great responsibilities and constant emotional tension. Therefore, it is necessary to acknowledge the risk factors for the development of this disorder. Thus, the present thesis gave rise to three articles and was elaborated with the aim of analyzing the profile, verifying the feeling of professional valorization and investigating the quality of working life (QWL) of veterinary doctors, identifying the prevalence of compassion fatigue or satisfaction in these professionals. Thus, a qualitative and quantitative research was carried out with veterinarians working in the direct care of patients in the city of Santa Maria/RS, Brazil. For this purpose, each participant answered an online questionnaire between June and July 2021, which contained two parts. The first part included questions on professional and sociodemographic characterization and the second one measured satisfaction or compassion fatigue according to the “Professional Quality of Life Scale” (ProQOL-BR). The contribution of this thesis consists of results that evidenced several work situations that originate stress in veterinarians, workers with signs of work exhaustion, feeling of devaluation, imbalance in the quality of professional life and prevalence of compassion fatigue. The identification of such situations is essential for the development of strategies for the search of better working conditions and quality of professional life.